A new aboreal species of sword-tailed cricket (Orthoptera: Trigonidiidae: Trigonidiinae) from the mangrove in Singapore - Tan, Ming Kai (Zootaxa, 2022)
Sword-tailed crickets of the genus Amusurgus Brunner von Wattenwyl, 1893 (Orthoptera: Trigonidiidae: Trigonidiinae) from Southeast Asia is still poorly known and its taxonomy requires a revision. Many species are still awaiting discovery and formal description. Based on newly-acquired materials from the mangrove in Singapore, a new species of Amusurgus is described: Amusurgus (Amusurgus) caerulus sp. nov. This discovery also demonstrates that even in a small country like Singapore, we still do not have a comprehensive understanding of its orthopteran diversity.